Variasi Genetik pada Marga Dicksonia Koleksi Kebun Raya Bali – Deteksi dengan PCR - SSCP - Wenni S. Lestari; Bayu Adjie (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
Dicksonia is one of tree ferns species that can be found in Indonesian highlands. Due to their wide distribution this species was suggested to have genetic variation among their population. Samples from Bali, West Java (Cibodas) and East Nusa Tenggara were compared using the PCR-SSCP methods to detect genetic variation of trnL-trnF intergenic spacer from the cpDNA plastid genome. Sample from Bali and West Java (Cibodas) did not morphologically and genetically variated, but they were variated to samples from East Nusa Tenggara.